Smart home application: Controlling a portable headphone amplifier's potentiometer through parallel port via internet / Daniel Leonard Henry - Daniel, Leonard Henry (2004)
Smart Homes are being build now at present and there are no doubts that they are having direct impacts on our life, even on the lifestyles of people living in these Smart Homes. The project uses parallel port programming to implement the Smart Home concept. This project comprises of two components, a software and hardware component. The software component consists of a client program and a server program. Both of these programs are connected remotely via the Internet or through a network environment. The client program allows the end user to control the application. The server program is connected to the hardware component using the parallel cable. The client program and server program will be written using Microsoft Visual C++. The hardware component acts as a volume control device. Here the hardware will control the volume of an audio amplifier. To do this, the hardware will control the volume of an audio amplifier. To do this, the hardware will resemble like a stepped attenuator. Electronic devices such as transistors and relays will be used.The integration of both so software and hardware will show that the end user is able to control a remotely situated parallel port, where the server program is controlling the data pins. By enabling and disabling the data pins on the parallel port, it is possible to control the volume of an audio amplifier by acting as a volume control switch.